Someone to care eaudiobook - Balogh, Mary (Westcott, 2018)
Once the Countess of Riverdale, Viola Kingsley throws all caution to the wind when adventure calls in the form of a handsome aristocrat.. Two years after the death of the Earl of Riverdale, his family has overcome the shame of being stripped of their titles and fortune-except for his onetime countess, Viola. With her children grown and herself no longer part of the social whirl of the ton, she is uncertain where to look for happiness-until quite by accident her path crosses once again with that of the Marquess of Dorchester, Marcel Lamarr. Marcel Lamarr has been a notorious womanizer since the death of his wife nearly twenty years earlier. Viola caught his eye when she herself was a young mother, but she evaded his seduction at the time. A prize that eluded him before, she is all the more irresistible to him now although he is surprised to discover that she is as eager now for the excitement he offers as he is himself. When the two defy convention and run away together, they discover that the ties of respectability are not so easily severed, and pleasure can ensnare you when you least expect it..